ASPEK PSIKOLOGI, SOSIAL-KULTURAL DAN SIKAP ISLAM TERHADAP PERILAKU TRANSEKSUAL DI INDONESIA - Widodo Winarso (FENOMENA, 2015)
The aspect of social issues becomes one of the concerns of contemporary Islam. This aspect is usually discussed and became the hottest news in social life. One might feel having lack of unanimity in the provision of public attitudes towards him/her self. This is what happened to transsexual and genital surgery people. Those who have and do the things that feel cornered because people assume the actions carried out under the assumption that they have been violated. Transsexual is a person whose way of behaving not same to the appearance of gender roles in general. Transsexual is a person who in the various levels of "breaking" cultural norms about how men and women should have it. A woman, for example, is culturally soft and tender. If a man has such kind of girl character, it's called transsexuals. Some transsexual people are wearing the opposite sex clothes. Transsexual people might change his or her gender, as male changes into a woman, and vice versa. Many things can affect the formation of transsexual behavior; from biological aspect, social-psychological, and cultural aspects. Muslims take a stand against the potential problems that may result from the presence of the transsexual behavior. In spite of these problems, Muslims should be wise in maintaining harmony in the social life of this world.